Walddegradation und Waldsanierung im Raum von Garmisch-Partenkirchen - Ehrig, Friedrich Reiner (ERDKUNDE, 1977)
Intensive grazing of forest lands until 1918, which has since decreased, combined with an increasingly excessive wildlife density resulted in extensive degradation of sub alpine mountainous forests as well as in considerable disturbance of lower mixed-stand forests in the upland mountainous landscape of southern Bavaria in the area of Garmisch-Partenkirchen. The substantial decline in the protective function of forest lands for valley areas was expressed by increasing soil erosion and uncontrolled mountain stream activity. Until now the efforts to control mountain torrents along with local reforestation, in order to stabilize this landscape, have been limited to objectoriented protection measures. Further degradation of forests due to recently increasing use of these areas for sheep grazing, while maintaining high wildlife densities can only be prevented by consistent application of so called “integral restoration of forest lands on a broad regional basis.